The Impact of Talent Management Strategies on Employee Performance: A Review - Sidek, Safiah; Al Hammadi, Ibraheem Hasan Thani; Al-Shami, Shamer Ali (Journal of Human Capital Development (JHCD), 2021)
The increasingly complexity and volatile environment of the current business context due to the advancement in technology and changes of workforce demographics have increased the need for organizations to identify, recruit and retain their talented employees. Talent management strategies become a priority for all organizations to ensure their competitive advantage. Recognizing its importance, an extensive research on talent management has been conducted by researchers, covering different emphasis. This paper aims to provide a review of research related to talent management and job performance. Drawn from an analysis of 20 related studies, several research gaps are identified, and these research gaps relate to the diversified perspectives and conceptualisation of talent management, the underpinning theories and the contexts and industrial sectors of research in talent management and the constructs and their relationships investigated in research of talent management. These findings are valuable for researchers to embark in future research on the impact of talent management strategies and job performance. Keywords: Talent management strategies; job performance; literature review; theories; constructs